MARKET, ENTREPRENEURIAL ORIENTATIONS AND PERFORMANCE OF SMEs HOTELS IN NANYUKI TOWN, KENYA - Nduriri, Mary Wanjira; Namusonge, Dr Mary (European Journal of Business and Strategic Management, 2017)
Purpose: The study sought to investigate the effect of market (MO) and entrepreneurial orientation (EO) on the performance of SMEs hotel enterprises in Nanyuki town, Kenya. Methodology: A sample size of 30 SMEs hotels who are registered with Laikipia County revenue collection office was selected using simple random sampling technique. 24 completed questionnaires were returned showing a response rate of 80%. Data was analyzed with the aid of statistical package for social sciences (SPSS) computer software. Correlation, Anova and Multiple regressions were the main analysis tools. Findings: The results of the study indicated that market and entrepreneurial orientations have a positive influence on the performance of the small-scale hotels. The six independent variables that were studied, explain 74.5 % of the performance of the SMEs hotels in Nanyuki town. Unique contribution to the theory, practice and policy: The policy makers will be able to obtain a clear guide on policy direction with respect to market and entrepreneurial orientation for further improvements of small and medium hotel enterprises in Kenya. Further, the study will increase the knowledge and awareness to the hotel managers on how to create customer value and enhance competitiveness within the small and medium hotel enterprises in Kenya. The studies on market and entrepreneurial orientations will help in improving small and medium enterprises and in particular hotel performance toward achieving Kenya's objectives of vision 2030.